2019
DOI: 10.1155/2019/8150736
|View full text |Cite
|
Sign up to set email alerts
|

Type of Preservation Solution, UW or HTK, Has an Impact on the Incidence of Biliary Stricture following Liver Transplantation: A Retrospective Study

Abstract: Organ preservation plays a crucial role in the outcome following solid organ transplantation. The aim of this study was to perform a retrospective outcome analysis following liver transplantation using histidine tryptophan ketoglutarate (HTK) or the University of Wisconsin (UW) solutions for liver graft preservation. We retrospectively reviewed data on adult patients who were liver-transplanted at Karolinska University Hospital between 2007 and 2015. There was evaluation of donor and recipient characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…Other studies have reported controversies about the role of preservative solutions in biliary complications. Studies by Karakoyun et al 26 and Heidenhain et al 27 reported an increased risk of biliary complications using the UW solution as compared with the HTK solution. However, other studies showed heterogeneous results and found that HTK solution was associated with an increased risk of biliary complications.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported controversies about the role of preservative solutions in biliary complications. Studies by Karakoyun et al 26 and Heidenhain et al 27 reported an increased risk of biliary complications using the UW solution as compared with the HTK solution. However, other studies showed heterogeneous results and found that HTK solution was associated with an increased risk of biliary complications.…”
Section: Discussionmentioning
confidence: 99%
“…HTK solution has been successfully used in organ preservation since the 1980s. The main advantage of the HTK solution is the lower risk of biliary complications in liver transplantation [ 42 ]. Histidine is a very potent buffer and in comparison to UW, HTK solution has very low viscosity and showed the same efficacy and safety profiles as UW in randomized prospective trials [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, preservation solutions with low viscosity have been postulated to improve liver washout during procurement and to better protect from IRI and its complications, such as graft dysfunction and post‐transplant cholangiopathy in particular [24,25]. HTK is characterized by low viscosity; nevertheless, its hypothesized beneficial effect on EAD was disproved in an earlier study of the UNOS database [26] and in a recent single‐center study [27], and the observations from our analyses point toward the same direction. IGL‐1 is also characterized by low viscosity, [28] and preliminary pre‐ and clinical studies suggested that IGL‐1 may be particularly suited for the flush out of the microcirculation, thereby reducing the occurrence of post‐transplant cholangiopathies [11,29–31].…”
Section: Discussionmentioning
confidence: 99%